2007
DOI: 10.2174/138161207782360717
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Targeted Therapies for Hepatocellular Cancer

Abstract: Present treatment options for hepatocellular cancer (HCC) are limited to those individuals with good liver function and early stage disease. Unfortunately this includes only a minority of patients, few of which are actually cured of their cancer. Over the last 15-20 years biotechnology has made a very significant impact on medical research, to the extent that we know very much more about the regulation of normal cell growth and death, as well as the mechanisms underlying its disruption in disease processes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…This study highlights the limitations of the current prognostic system, even after correction for the response to treatment. Our findings support a growing body of literature that emphasizes the variable biological nature of individual hepatomas24‐28 and calls for further efforts to find superior biological predictors. Genomic and proteomic advances in the field have further defined the natural history of HCC and will aid in pretransplant and posttransplant prognostication 28.…”
Section: Discussionsupporting
confidence: 82%
“…This study highlights the limitations of the current prognostic system, even after correction for the response to treatment. Our findings support a growing body of literature that emphasizes the variable biological nature of individual hepatomas24‐28 and calls for further efforts to find superior biological predictors. Genomic and proteomic advances in the field have further defined the natural history of HCC and will aid in pretransplant and posttransplant prognostication 28.…”
Section: Discussionsupporting
confidence: 82%
“…IFNα has also been proposed both in the prevention and treatment of HCC (Chattopadhyay et al , 2007). Although the impact of IFN-based therapies to prevent HCC development in cirrhotic patients is still highly controversial (Craxì and Cammà, 2005; Shiratori et al , 2005; Lok et al , 2009), recent studies have shown clinical efficacy of IFNα alone and in combination with chemotherapeutic agents in the treatment of advanced HCCs with portal vein tumor thrombosis and/or extrahepatic metastasis (Obi et al , 2006; Uka et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…IFNs have been used with varying effectiveness as proapoptotic agents in the treatment of malignancies, as e.g., myeloma (3), renal (4), or bladder cancer (5), and there is increasing evidence of effectiveness of IFNs in the treatment and prevention of HCC. Recent studies show that IFNs, in combination with chemotherapeutics (6) or agents such as proteasome inhibitors (7,8), may prove to be clinically effective. It has been reported that IFN therapy, even after curative treatment of HCC, could prevent HCC recurrence and improve survival.…”
Section: Introductionmentioning
confidence: 99%